2014
DOI: 10.4172/2329-888x.1000126
|View full text |Cite
|
Sign up to set email alerts
|

Longevity in Dairy Cattle

Abstract: Longevity of productive life in dairy cattle is a characteristic difficult to evaluate. This measurement is complicated, in part, because the phenotype is expressed late in the life of the animal, but also because the methods of evaluation are complex. The molecular bases of longevity are still far from being fully understood, although some genes begin to be associated with this characteristic. In this short communication will be discussed the criteria for selection in dairy cattle and to report some studies e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…Herd management is a key factor in minimizing the decline in functional traits and improving longevity (de Mello et al, 2014), but longevity is also influenced by genetics. Heritability estimates for longevity are highly dependent on how it is analyzed; reported estimates range from 0.03 to 0.39 (Roxström and Strandberg, 2002;SEGES, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Herd management is a key factor in minimizing the decline in functional traits and improving longevity (de Mello et al, 2014), but longevity is also influenced by genetics. Heritability estimates for longevity are highly dependent on how it is analyzed; reported estimates range from 0.03 to 0.39 (Roxström and Strandberg, 2002;SEGES, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although PL is primarily affected by environmental effects such as year and age at first calving, season, and herd, it also has a genetic component. Most studies reported low heritability for PL, but estimates depended on the model used for estimating genetic variation [ 44 , 45 , 46 ]. Due to the fact that heritability estimates for type traits generally ranged from moderate to high, indirect selection could be useful for economic traits of interest that have a strong genetic correlation with type traits [ 14 , 18 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of lameness both genetic and phenotypic correlations were significant, which suggests that farmers were failing to hold the line. In recognition of the genetic link between selection policies heavily weighted toward increased yield, breeding companies have reformulated their selection indices to give increased emphasis to traits defined as robust as measured by an increase in productive life span (De Mello et al, 2014). In the selection index currently used by the UK Independent Dairy Breeding Company nearly 70% of traits are now based on measures of fitness, longevity and good welfare.…”
Section: An Unkind Dairy Industry? Intensive Dairy Production Is Incompatible With Animal Welfarementioning
confidence: 99%